Identification and Characterization of Small-Molecule Inhibitors of the R132H/R132H Mutant Isocitrate Dehydrogenase 1 Homodimer and R132H/Wild-Type Heterodimer. (September 2014) - Brooks, Eric; Wu, Xiang; Hanel, Art; Nguyen, Shaun; Wang, Jing; Zhang, Jeffrey H.; Harrison, Amanda; Zhang, Wentao
Recurrent genetic mutations in isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) have been identified in multiple tumor types. The most frequent mutation, IDH1 R132H, is a gain-of-function mutation resulting in an enzyme-catalyzing conversion of α-ketoglutarate (α-KG) to 2-hydroxyglutarate (2-HG). A high-throughput assay quantifying consumption of NADPH by IDH1 R132H has been optimized and implemented to screen 3 million compounds in 1536-well formats. The primary high-throughput screening hits were further characterized by RapidFire–mass spectrometry measuring 2-HG directly. Multiple distinct chemotypes were identified with nanomolar potencies (6–300 nM). All inhibitors were found to be inactive against the wild-type IDH1 homodimers. An IDH1 heterodimer between wild-type and R132H mutant is capable of catalyzing conversion of α-KG to 2-HG and isocitrate to α-KG. Interestingly, one of the inhibitors, EXEL-9324, was found to inhibit both conversions by the IDH1 heterodimer. This indicates the R132H/WT heterodimer may adopt conformations distinct from that of the R132H/R132H homodimer. Further enzymatic studies support this conclusion as the heterodimer exhibited a significantly lower apparent Michaelis-Menten constant for α-KG (Km =110 µM) compared with the R132H homodimer (Km = 1200 µM). The enhanced apparent affinity for α-KG suggests R132H/WT heterodimeric IDH1 can produce 2-HG more efficiently at normal intracellular levels of α-KG (approximately 100 µM).